Our toxic world a guide to hazardous substances in our everyday lives - Gupta, Aniruddha Sen; Kuriyan, Priya; Toxics Link (Organization : India). (New Delhi, India SAGE, 2010)
The mode of development that the worldand Indiahas followed has led to a situation where we are surrounded by numerous hazardous substances in our everyday lives, which affect the health of people, of other living creatures, and of the planet as a whole. Our Toxic World is an effort to shine a keen light on these substances, and suggest alternatives that will allow readers to improve the physical quality of their lives and of their environment. Our Toxic World takes a series of peeks into the lives of the fictitious Sachdeva family and the people they come in contact with, examines the hazardous substances that affect us in our everyday lives, outlines the effect these materials can have on us, and suggests alternative routes that we can adopt
Title from title screen (viewed October 20, 2023)
Specialized
Description based on print version record
Keywords: Environmental health; Environmental toxicology